Análise da vulnerabilidade natural da paisagem em relação aos diferentes níveis de ocupação da bacia hidrográfica do Rio Vermelho, Estado de Goiás / Analysis of the landscape natural vulnerability relatively to the differente levels of occupation in the Rio Vermelho watershed, Goiás State, Brazil. - Pedro Alves Vieira; Nilson Clementino Ferreira; Laerte Guimarães Ferreira (Sociedade & Natureza)
The Rio Vermelho watershed, located in the Goiás State, shows a great geodiversity, with terrains ranging from the Arquean to the Holocene, in addition to a proeminent tectonic record. Likewise, throughout its occupation history, it has been impacted by a variety of surface and underground activities, which resulted in biodiversity impovereshment, as well as physical modifications, particularly progressive erosion processes and sediment accumulation, as a function of the dynamic incoming and outcoming of matter and energy from the natural system. In this work, based on the elaboration and analysis of an entropy map for the entire basin area (~ 11,000 km2), it was possible to identify areas more susceptible to morphogenetic processes and, therefore, more vulnerable to land use and occupation. As an example of such areas, are those near the basin delta, where entropy values are compatible with the diversity of land uses and interventions over the complex fluvial system around the main Rio Vermelho channel. In spite the need of further analysis, at more detailed scales, our results clearly demonstrate the potential of the landscape entropy as an important tool for the identification of areas with more potential energy available for the geomorphological work and, therefore, more vulnerable to occupation (i.e. subject to floods and landslides).